FAKTOR-FAKTOR YANG MEMPENGARUHI KECURANGAN LAPORAN KEUANGAN : STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR SUBSEKTOR FOOD & BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Meidiyustiani, Rinny; Nopaludin, Nopaludin (Yayasan Education and Social Center, 2024)
This study was conducted to analyze the factors that influence financial statement fraud. This research was conducted at food &beverage subsector manufacturing companies listed on the Indonesia Stock Exchange for the period 2016-2020. The sample determination method in this study used the purposive sampling method with a sample of 19 food &beverage subsector manufacturing companies that had met the sample criteria. The study used multiple linear regression analysis techniques and used the SPSS version 22.0 statistical test tool. The results of this study showed that financial target and external pressure variables had a positive and significant effect on the detection of financial statement fraud and audit opinions had a negative and significant effect on the detection of financial statement fraud, but the variables of financial stability, nature of industry, and change of directors had no effect on the detection of financial statement fraud